Transmission of tuberculosis in an incarcerated population during the subclinical period: A cross-sectional study in Qingdao, China - Wang, Zhongdong; Li, Haoran; Song, Song; Sun, Haiyan; Dai, Xiaoqi; Chen, Meng; Xu, Honghong; Zhang, Huaqiang; Pang, Yu (Frontiers in Public Health, 2023)
Objectives: As a closed gathering place, prison is the cradle of tuberculosis (TB) outbreak. Therefore, the analysis of the prevalence rate and risk factors of latent tuberculosis infection (LTBI) in prison will be a necessary measure to intervene in the spread of tuberculosis. Methods: In this study, we consecutively recruited 506 adult prisoners in Qingdao to carry out this cross-sectional study. TB and LTBI were screened by IGRA, X-ray, X-pert, sputum smear and culture. Results: A total of 17 TB,101 LTBI and 388 HC were identified, with an infection rate of 23.32% (118/506) and a TB incidence rate of 3282/100,000 population. Age, malnutrition and inmates living with TB prisoners were risk factors for LTBI. Additionally, most TB cases (70.59%, 12/17) were subclinical tuberculosis (STB), contributing significantly to TB transmission. Conclusion: Our results demonstrate that the transmission efficiency of asymptomatic patients is not essentially different from that of symptomatic patients, indicating that TB transmission occurs during the subclinical period. Our findings highlight the need to strengthen active case-finding strategies to increase TB case detection in this population.